Consciously Constructing the Robust NiS/g-C3N4 Hybrids for Enhanced Photocatalytic Hydrogen Evolution - Lin, Xiao; Du, Shiwen; Li, Chunhe; Li, Guojun; Li, Youji; Chen, Feitai; Fang, Pengfei (Catalysis letters, 2020)
Selective growth of cocatalyst on the surface of photocatalyst has been attracted considerable attention due to their efficient charges transfer property. In this study, the robust NiS modified graphitic carbon nitride (g-C 3 N 4 ) hybrids were successfully synthesized by a facile surface photochemical deposition process. The structure and composition characterization results revealed that the NiS is highly dispersed loading on the surface of g-C 3 N 4 nanosheets, and the NiS/g-C 3 N 4 hybrids possess large surface areas and excellent optical properties. Under the visible light illumination, the NiS/g-C 3 N 4 hybrids with 1.0% weight content of NiS cocatalyst exhibits the highest hydrogen evolution rate of 1346.1 μmol h −1 g −1 with an apparent quantum efficiency (AQE) of 7.67%. On the basis of photoluminescence (PL) spectra and photoelectrochemical methodology, the photocatalytic hydrogen evolution mechanism was proposed. The results demonstrated that the excellent activity arises from the strong electronic coupling, highly efficient charges separation and migration. This work demonstrates a facile photochemical deposition method to consciously construct the robust two-dimensional (2D) hybrids, so as to realize accurate deposition of cocatalyst and efficient migration of photo-generated carriers. Graphic Abstract